Concretization of the direction of formation of artistry among female rhythmic gymnasts based on taking into account factors of success in creating a motor image to music - Soboleva E.A. (Theory and Practice of Physical Culture, 2025)
The article is devoted to specifying the factors of success in creating a motor image to music, as well as developing approaches to the formation of artistry of athletes in rhythmic gymnastics at the stage of initial training, based on the trends in the development of rhythmic gymnastics and the psychophysiological characteristics of athletes.